Comparative transcriptomics reveals RhoE as a novel regulator of actin dynamics in bone-resorbing osteoclasts - Georgess, Dan (2014)
The function of osteoclasts (OCs), multinucleated giant cells (MGCs) of the monocytic lineage, is bone resorption. To resorb bone, OCs form podosomes. These are actin-rich adhesive structures that pattern into rings that drive OC migration and into “sealing-zones” (SZs) that confine the resorption lacuna. Although changes in actin dynamics during podosome patterning have been documented, the mechanisms that regulate these changes are largely unknown. From human monocytic precursors, we differentiated MGCs that express OC degradation enzymes but are unable to resorb the mineral matrix. We demonstrated that, despite exhibiting bona fide podosomes, these cells presented dysfunctional SZs. We then performed two-step differential transcriptomic profiling of bone-resorbing OCs versus nonresorbing MGCs to generate a list of genes implicated in bone resorption. From this list of candidate genes, we investigated the role of Rho/Rnd3. Using primary RhoE-deficient OCs, we demonstrated that RhoE is indispensable for OC migration and bone resorption by maintaining fast actin turnover in podosomes. We further showed that RhoE activates podosome component cofilin by inhibiting its Rock-mediated phosphorylation. We conclude that the RhoE-Rock-cofilin pathway, by promoting podosome dynamics and patterning, is central for OC migration, SZ formation, and, ultimately, bone resorption.